Genome-wide analysis of the Cannabis sativa cytochrome P450 monooxygenase superfamily and uncovering candidate genes for improved herbicide tolerance - Kaur, Navneet; Verma, Awadhesh Kumar; Girdhar, Madhuri; Kumar, Anil; Siddiqui, Maqsood A.; Al-Khedhairy, Abdulaziz A.; Malik, Tabarak; Mohan, Anand (Frontiers in Plant Science, 2024)
Cannabis sativa is an economically important crop, yet weed management remains a significant challenge due to limited herbicide options. Cytochrome P450 enzymes play crucial roles in plant metabolism, including herbicide detoxification. This study aimed to identify and characterize the CYP gene family in Cannabis and investigate their potential role in herbicide metabolism. We identified 225 CYP proteins encoded by 221 genes in the Cannabis genome, classified into 9 clans and 47 families. The majority of CsCYPs were predicted to be located in endomembrane system and chromosomal mapping revealed that they were present in all the chromosomes. Motif and gene structure analysis supported the results from phylogenetic analysis. The gene duplication analysis results showed that tandem duplication plays a pivotal role in evolutionary expansion of CsCYP superfamily. Promoter analysis revealed various cis-acting elements involved in stress, light, hormone and development responses. Molecular docking simulations identified several CsCYPs with strong binding affinities to ALS-inhibiting herbicides, particularly bispyribac-sodium, propoxycarbazone-sodium, and pyriftalid. CsCYP_215, CsCYP_213, CsCYP_217 and CsCYP_14 emerged as promising candidates for herbicide metabolism. Analysis of binding site residues revealed the importance of hydrophobic and aromatic interactions in herbicide binding. This study provides the first comprehensive characterization of the CYP gene family in C. sativa and offers new insights into their potential roles in herbicide metabolism. The identification of promising herbicide-metabolizing CYP candidates opens new avenues for developing herbicide-tolerant Cannabis varieties, potentially addressing key challenges in weed management and crop productivity.